Menjaga Warisan Budaya: Minat Generasi Muda Batak Toba dalam Menjadi Raja Parhata - Nainggolan, Ceria Terresa (Innovative: Journal Of Social Science Research, 2025)
Raja Parhata has a central role in the customs of the Batak Toba as a leader in traditional ceremonies and guardian of cultural values. However, in the midst of modernization, concerns have arisen regarding the interest of the younger generation in continuing this role. This study aims to analyze the extent of the interest of the younger generation of the Batak Toba in becoming Raja Parhata and the factors that influence this interest. The research method used is a qualitative approach with interview and observation techniques of the younger generation and traditional figures in the Batak Toba community. The results of the study indicate that although there are still young people who are interested in becoming Raja Parhata, challenges such as lack of understanding of customs, the influence of outside culture, and changes in modern lifestyles are inhibiting factors. Therefore, revitalization efforts are needed through cultural education, active family roles, and strengthening traditional communities so that the regeneration of the role of Raja Parhata can continue.